A qualitative study to understand sociocultural beliefs around perinatal and neonatal health in rural areas of Mohali, Punjab, India - Ahuja, Alka; Duggal, Mona; Liu, Jane Y.; Sharma, Preetika; Hosapatna Basavarajappa, Darshan; Bagga, Rashmi; El Ayadi, Alison M.; Kankaria, Ankita; Kumar, Vijay; Singh, Pushpendra; Diamond-Smith, Nadia G. (Frontiers in Global Women's Health, 2023)
Introduction Globally, 600,000 mothers (15-49 years) die every year due to pregnancy and childbirth-related complications. Wide variations are seen in cultural practices and beliefs surrounding this period of a woman's life. The present study explores the cultural beliefs and practices of women and families during pregnancy and the postnatal period in order to understand what behavioral management strategies are required to improve maternal and infant outcomes during pregnancy and the postpartum period. Methods The study was conducted in a rural area of Punjab, from December 2019 to March 2021. A total of 20 women (up to 3 months postpartum, age >18 years, were interviewed. Results In general, women described eating varied and fairly healthy diets during pregnancy, especially nutritious warm food, following traditional practices. Other cultural practices included restrictions on movement and mobile phone use and the use of unsafe home remedies to promote infant safety and wellbeing, such as using gripe water, applying black pencil to the baby's eyes, and feeding the baby honey. A few were not inclined to engage with these and other cultural expectations, preferring instead to follow contemporary practices influenced by social media. These practices included being accompanied by a family member during delivery, celebrating the baby's birth regardless of sex, and early bathing post-delivery. Discussion It can be concluded that while many traditional practices are still followed in India, there are new beliefs and behaviors arising from an intersection between culture and technology. Developing strategies that acknowledge older beliefs and modern approaches is essential to promoting better antenatal and postpartum care.